2020
DOI: 10.1093/mnras/staa1012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling a bright z = 6 galaxy at the faint end of the AGN luminosity function

Abstract: Recent deep surveys have unravelled a population of faint active galactic nuclei (AGN) in the high redshift Universe, leading to various discussions on their nature and their role during the Epoch of Reionization. We use cosmological radiation-hydrodynamics simulations of a bright galaxy at z ∼ 6 (M 10 10 M ) hosting an actively growing super-massive black hole to study the properties of these objects. In particular, we study how the black hole and the galaxy co-evolve and what is the relative contribution of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 93 publications
(145 reference statements)
4
20
0
Order By: Relevance
“…5.5 we show the main results of the paper for Si ii λ1260. Here we use one galaxy from a zoom-in simulation, and in future work we will study a statistical sample of galaxies from various simulations like Sphinx 1 (Rosdahl et al 2018) or Obelisk (Trebitsch et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5.5 we show the main results of the paper for Si ii λ1260. Here we use one galaxy from a zoom-in simulation, and in future work we will study a statistical sample of galaxies from various simulations like Sphinx 1 (Rosdahl et al 2018) or Obelisk (Trebitsch et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The main candidates for the source of reionization are active galactic nuclei (AGNs) and massive stars. Although recent work suggests AGNs could be an important driver of reionization (Madau & Haardt 2015;Giallongo et al 2019), a consensus seems to be emerging on the idea that their contribution is negligible compared to that of stars (Grissom et al 2014;Parsa et al 2018;Trebitsch et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the literature has shown contrasting results, with some works suggesting a significant contribution of AGN to reionization (e.g. Mitra et al 2018;Grazian et al 2018;Finkelstein et al 2019), while others found it to be largely subdominant (Onoue et al 2017;Qin et al 2017;Hassan et al 2018;Trebitsch et al 2018Trebitsch et al , 2020. Dayal et al (2020), using the Delphi semi-analytic model (SAM) presented in this thesis, found INTRODUCTION that AGN account for about 10´25% of the total amount of ionising photons at z ě 4.…”
Section: The Sources Of Reionizationmentioning
confidence: 81%
“…Despite the fact that the spin parameter of the black hole is tracked, the radiative efficiency is fixed at 10%, and both the quasar and radio feedback modes are implemented. On a sub-volume of this same simulation, Trebitsch et al (2020) built the OBELISK simulation, an attempt to bridge the gap between large-volume cosmological simulations and high-resolution zoom-in studies, managing to study at the same time reionization evolution and halos just above the atomic-cooling limit. The EAGLE simulation (Crain et al 2015;Schaye et al 2015) is based on the SPH code GADGET (Springel 2005).…”
Section: Theoretical Methods For Black Holes In a Cosmological Contextmentioning
confidence: 99%
See 1 more Smart Citation